Pantheism in wordsworth: a study from the Islamic perspective - Muhammad Azizul Hoque, (Universiti Kebangsaan Malaysia, 2014)
William Wordsworth, a literary icon in romantic poetry, has impressed us with his pantheism and therefore, encouraged us to think of doing research into the concept with some modifications from Islamic perspective. It is, indeed, difficult to analyse the idea from Islamic perspective, because holding multidimensional concepts of God, and contradictory theories and hypotheses by some Muslim pundits and Sufis basing the concepts of other religions and ideas of God instead of authentic sources from the Holy Quran and Hadith, have made the general Muslims confused. Moreover, ideas like these may lead the believers to the Shirk (partnership) with God. So we have attempted to analyse the concept of the romantic poet along with the related concepts of some Sufis in the light of Islam with the support of some Qur’anic verses.